Impaired theta and low-gamma directed information flow in the hippocampal-prefrontal circuit underlies working memory deficits in APP/PS1 mice - Hongrui Ai; Shengnan Zhang; Chengbo Si; Tiaotiao Liu; Xuyuan Zheng; Xin Tian; Wenwen Bai (Behavioral and Brain Functions)
Abstract Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline. Working memory impairment, a hallmark of early-stage AD, is hypothesized to arise from deficits in encoding processes. Given the critical role of hippocampal-prefrontal interactions in working memory, we investigated whether disrupted encoding mechanisms in this circuit contribute to AD-related deficits. We performed simultaneous local field potential (LFP) recordings in the ventral hippocampus (vHPC) and medial prefrontal cortex (mPFC) of APP/PS1 transgenic mice during a spatial working memory task. We analyzed oscillatory dynamics and directed information flow between these two regions across distinct task phases. Wild-type mice exhibited task-phase-specific enhancement of theta (4–12 Hz) and low-gamma (30–40 Hz) information flow from vHPC to mPFC during encoding, which correlated with performance accuracy. APP/PS1 mice showed a significant reduction in the theta and low-gamma flow and impaired task performance. Decoding analyses revealed a robust correlation between the strength of directed information flow and performance accuracy. These findings provide compelling evidence for a neurophysiological mechanism linking vHPC-mPFC circuit dynamics to encoding processes, offering new insights into the neural basis of working memory impairment in AD.